Chemopreventive activity of apple extract following medium-term oral carcinogenesis assay induced by 4-nitroquinoline-1-oxide - Pidone Ribeiro, Flavia Andressa; Gomes de Moura, Carolina Foot; Boiago Gollucke, Andrea Pitelli; Ferreira, Monica Siqueira; Catharino, Rodrigo Ramos; Aguiar, Odair; Spadari, Regina Celia; Barbisan, Luis Fernando [UNESP]; Ribeiro, Daniel Araki (Elsevier B.V., 2014)
Objective: The aim of this study was to evaluate the chemopreventive activity of an apple extract following medium-term oral carcinogenesis assay induced by 4-nitroquinoline-1-oxide (4NQO).Methods: A total of 30 male Wistar rats were distributed into five groups as follows (n = 6 per group): Group 1, negative control group (non-treated group); Group 2, received 4NQO during 8 weeks in drinking water and treated with apple extract at 1% by gavage between the first and fourth weeks daily (initiation phase); Group 3, received 4NQO for 8 weeks in drinking water and treated with apple extract by gavage at 1% between the fifth and eighth weeks daily (promotion phase); Group 4, received apple extract at 1% by gavage for 8 consecutive weeks only; and Group 5, received 4NQO for 8 weeks in drinking water daily.Results: Histopathological analysis revealed decreased hyperplasic lesions in Group 2 when compared with Group 5. Likewise, decreased dysplastic lesions in Group 3 were observed when compared with Group 5. In Groups 2 and 3, decreased COX-2 and TNF-alpha gene expressions were observed when compared with Group 5. Cytochrome c and caspase 3 levels increased in Groups 2 and 3 when compared with Group 5.Conclusion: In conclusion, our results demonstrate that apple extract suppresses rat tongue carcinogenesis as a result of anti-inflammatory activity and apoptosis through the intrinsic mitochondrial pathway. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Apple extract; 4-Nitroquinoline-1-oxide; Oral cancer; Inflammation; Apoptosis